Changes in ruminal microbial populations in transition dairy cows - Park, A.F.; Titgemeyer, Evan C.; Cochran, R.C.; DeFrain, J.M.; Ferdinand, E.E.; Wallace, N.; Nagaraja, Tiruvoor G.; Johnson, D.E.; Shirley, John E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We used four ruminally fistulated, multiparous, pregnant Holstein cows to delineate microbial adaptations in dairy cows as they experienced the transition from one lactation to the next. Diets consisted of typical far-off and close-up diets, a late lactation diet containing wet corn gluten feed (20% DM) and an alfalfa hay-corn silage based early lactation diet. Calculated NEL (Mcal/lb), measured crude protein (%), and diet digestibilities (%; based on steers fed at 2% of BW) were: 0.78, 18.7, 74.1; 0.70, 11.5, 66.2; 0.74, 15.6, 71.0; 0.73, 18.4, 70.7 for late lactation, far-off dry, close-up dry, and early lactation, respectively. Microbial samples were obtained on days 72 (late lactation), 51 (far-off dry), 23, and 9 (close-up dry) prepartum and days 6, 20, 34, 48, 62, 76, and 90 postpartum. We analyzed ruminal samples for ciliated protozoa and viable counts of bacteria and fungi. Changing from a high forage to a high concentrate diet impacted bacterial counts less than ciliated protozoal and fungal counts. Switching diets from high concentrate to high forage increased ciliated protozoa and fungal counts, and counts decreased when diets were switched from high forage to high concentrate. Bacterial and ciliated protozoa counts increased in early lactation and decreased as cows approached peak dry matter intake. Dietary changes with the onset of lactation led to virtual disappearance of fungi from the rumen. In general, ruminal microbial populations of dairy cows respond to changes in diet and intake. Changes in diet affected populations of protozoa and fungi, whereas changes in intake affected populations of bacteria, protozoa, and fungi.
Keywords: Dairy; Transition; Dairy cow; Microbial